Characteristics and Outcomes of Unexecuted Postpartum Sterilization in High Risk Low Income Obstetrical Patients [10R]. (May 2018) - Persad, Malini D.; Staszewski, Cara; Ly, Victoria; Garry, David; Quirk, J. Gerald
Abstract : INTRODUCTION: To determine the characteristics and outcomes associated with unexecuted postpartum sterilizations in high risk low income obstetrical patients. METHODS: A retrospective cohort study of pregnant women desiring postpartum sterilization from a high risk, Medicaid based, obstetrical practice was undertaken at a university based hospital from January-June 2014. Women who did not undergo postpartum sterilization were compared to those who underwent the postpartum procedure during the hospital stay. Maternal demographic factors, medical history, obstetrical history and mode of delivery were extracted from the medical record. Women who did not undergo sterilization were assessed for contraception utilized, obstetrical follow up, unintended pregnancy rate and subsequent adverse pregnancy outcomes. Groups were compared with the use of parametric and non-parametric tests with a p <0.05 as statistically significant. RESULTS: Over the 6-month period, 73 high risk low income women were identified, with 40% failing to undergo postpartum sterilization during their hospital stay. Women were less likely to undergo sterilization if they were younger, single, and had a vaginal birth. In those not undergoing the procedure, 31.0% received an alternative form of contraception, 6.9% received interval sterilization, 27.5% had unintended pregnancies of which 12.5% had a subsequent adverse pregnancy outcome and 31.0% were lost to follow up. CONCLUSION: Failure to perform postpartum sterilization results in a high unintended pregnancy rate and adverse subsequent pregnancy outcomes. In those with unfulfilled procedures, efforts should be made to provide alternative contraception and planned follow up prior to discharge.